Eukaryotic RNA Polymerases: The Many Ways to Transcribe a Gene - Barba-Aliaga, Marina; Alepuz, Paula; Pérez-Ortín, José E. (Frontiers in Molecular Biosciences, 2021)
In eukaryotic cells, three nuclear RNA polymerases carry out the transcription from DNA to RNA, and they all seem to have evolved from a single enzyme present in the common ancestor with archaea. The multiplicity of eukaryotic RNA polymerases allows each one to remain specialized in the synthesis of a subset of transcripts, which are different in the function, length, cell abundance, diversity and promoter organization of the corresponding genes. We hypothesize that this specialization of RNA polymerases has conditioned the evolution of the regulatory mechanisms used to transcribe each gene subset to cope with environmental changes. We herein present the example of the homeostatic regulation of transcript levels versus changes in cell volume. We propose that the diversity and instability of messenger RNAs (mRNAs), transcribed by RNA polymerase II have conditioned the appearance of regulatory mechanisms based on different gene promoter strength and mRNA stability. However for the regulation of ribosomal RNA (rRNA) levels, which are very stable and transcribed mainly by RNA polymerase I from only one promoter, different mechanisms act based on gene copy variation and a much simpler regulation of the synthesis rate.